Activity and crowing frequency of Ayam Kokok Balenggek from West Sumatra by using and without perch - Arlina, Firda; Rusfidra, Rusfidra; Munafri, Sastra; Tanjung, Wahyuni Fauziah; Ardiansyah, Triwahyu; Rafian, Teguh (Journal of Advanced Veterinary Research, 2025)
Animal conservation is included in the Sustainable Development Goals (SDGs) as a genetic resource, one of which is namely Ayam Kokok Balenggek (AKB). AKB is a unique and distinctive crowing sound from West Sumatra, Indonesia, often featured in contests. This study aims to investigate the activities and crowing frequencies of AKB by using and without perch. The total eight mature male AKBs aged 1.5 and 2 years used in this study. The samples were divided into 2 categories based on the class in the AKB contest, namely the ‘landik’ and ‘boko’ categories The variables included eight activities and crowing frequency. The data analysis in this study was descriptive statistical analysis and the crowing frequency was subjected to a t-test analysis. The t-test results on the crowing frequency of the ‘landik’ and ‘Boko’ classes of AKB between perched and without perched was a highly significant difference (P<0.01). The results revealed that when perched, AKB exhibited 13% crowing activity, 17% wing flapping, and 34% feather pecking, which was notably higher compared to when they were without perched. The crowing frequency significantly (P˂0.01) distinct of Boko class AKBs when perched was 36% higher compared to without perches, while the landik class was 59% higher than without perches. The crowing activity and frequency, wing flapping, feather pecking, and frequency of AKB are higher when they are perched. The information from the study is an attempt to converse AKB with a unique sound and will be used as a guide when AKB contests are implemented.